2015
DOI: 10.7205/milmed-d-14-00039
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in the Military Health System Based on Electronic Health Data, 2009–2012

Abstract: Metabolic syndrome prevalence in the United States rose from 27% to 34.2% between 1999-2000 and 1999-2006. However, prevalence has not been determined in the Military Health System. This retrospective descriptive study included enrolled Military Health System adults during fiscal years 2009-2012. We explored three populations (nonactive duty, active duty, and Air Force active duty) and their metabolic syndrome components (body mass index or waist circumference, blood glucose test, triglyceride, high density li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The prevalence of MS in military personnel was significantly lower than that of the general population. 21 Soldiers tend to have higher BP and smoke more but have better lipid profile, fasting glucose and lower BMI than the general public. 17 However, the prevalence of MS in military personnel in the current study was significantly lower than other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MS in military personnel was significantly lower than that of the general population. 21 Soldiers tend to have higher BP and smoke more but have better lipid profile, fasting glucose and lower BMI than the general public. 17 However, the prevalence of MS in military personnel in the current study was significantly lower than other studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to random effect meta-analysis, the rates of the global pooled prevalence (95% confidence interval) of MetS, high LDL, high TC, high TG, low HDL and high FBS were 21% (17-25), 32% (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), 34% (10-57), 24% (16-31), 28% and 9% (5-12), respectively. Moreover, the rates of the global estimated pooled prevalence of overweight, generalized obesity, abdominal obesity and HTN were 35% (31-39), 14% (13)(14)(15)(16), 29% (20-39) and 26% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), respectively. Figure 2 shows a forest plot of eligible articles for the estimation of MetS prevalence.…”
Section: Meta-analysismentioning
confidence: 99%
“…For both genders in the active duty population, the component threshold prevalence was described to increase with increasing age for all components except HDL-C while the trend for the nonactive duty population was less clear, making a reference to our study observations difficult. Herzog et al (2015) report active duty MetS prevalence was higher among men and highest in the 45-64 age group for both genders in the active duty sample. An important comment by the researchers described the strength in the study recognizing the "impact of the healthy worker effect in active duty on MetS prevalence" which followed with their separation of active and nonactive duty populations for analyses (Herzog et al, 2015).…”
Section: Indicators Of Metsmentioning
confidence: 66%
“…An important comment by the researchers described the strength in the study recognizing the "impact of the healthy worker effect in active duty on MetS prevalence" which followed with their separation of active and nonactive duty populations for analyses (Herzog et al, 2015). Although the nonactive duty sample was not representative of the nonactive population, the study importantly reported that trends of prevalence which still elucidate the percentages of the populations exceeding various MetS component thresholds which the researchers hope will lend to future "effective prevention, intervention, and disease management strategies" (Herzog et al, 2015).…”
Section: Indicators Of Metsmentioning
confidence: 99%
See 1 more Smart Citation